De novo copy number variants identify new genes and loci in isolated sporadic tetralogy of Fallot - Greenway, Steven C; Pereira, Alexandre C; Lin, Jennifer C; DePalma, Steven R; Israel, Samuel J; Mesquita, Sonia M; Ergul, Emel; Conta, Jessie H; Korn, Joshua M; McCarroll, Steven A; Gorham, Joshua M; Gabriel, Stacey; et al. (Nature genetics, 2009)
Christine Seidman and colleagues report that 1% of individuals with sporadic non-syndromic tetralogy of Fallot show copy number gains or losses at chromosome 1q21.1. They also report copy number changes at other loci that likely contribute to the etiology of this congenital heart malformation. Tetralogy of Fallot (TOF), the most common severe congenital heart malformation, occurs sporadically, without other anomaly, and from unknown cause in 70% of cases. Through a genome-wide survey of 114 subjects with TOF and their unaffected parents, we identified 11 de novo copy number variants (CNVs) that were absent or extremely rare (<0.1%) in 2,265 controls. We then examined a second, independent TOF cohort ( n = 398) for additional CNVs at these loci. We identified CNVs at chromosome 1q21.1 in 1% (5/512, P = 0.0002, OR = 22.3) of nonsyndromic sporadic TOF cases. We also identified recurrent CNVs at 3p25.1, 7p21.3 and 22q11.2. CNVs in a single subject with TOF occurred at six loci, two that encode known ( NOTCH1 , JAG1 ) disease-associated genes. Our findings predict that at least 10% (4.5–15.5%, 95% confidence interval) of sporadic nonsyndromic TOF cases result from de novo CNVs and suggest that mutations within these loci might be etiologic in other cases of TOF.